A Juvenile Specimen of Archaeorhynchus Sheds New Light on the Ontogeny of Basal Euornithines - Foth, Christian; Wang, Shiying; Spindler, Frederik; Lin, Youhai; Yang, Rui (Frontiers in Earth Science, 2021)
The ontogenetic development of extant birds is characterized by rapid growth, bone fusion and an early onset of flight ability. In contrast, little is known about how these ontogenetic traits evolved in the bird stem lineage, and the available data pertains primarily to Enantiornithes. Here, we describe an almost complete skeleton of a juvenile euornithine bird (LNTU-WLMP-18) from the Early Cretaceous Jiufotang Formation (Aptian), which was discovered near Lamadong Town (Jianchang County, Liaoning, China). Despite its completeness, bone preservation is rather poor. Thus, to increase the contrast between bone tissue and matrix, we used cyan-red-based autofluorescence photography. The specimen is more or less articulated and exposed in ventral aspect. The jaws are edentulous, the coracoid bears a procoracoid process, and the ischium lacks a proximodorsal process. The pedal unguals are short and barely curved, indicating a ground-dwelling lifestyle. Feathers, including long primaries, are present as carbonized traces. Several characters indicate that LNTU-WLMP-18 is a juvenile: the bone surface has a coarsely striated texture and no fusion is evident between the carpals and metacarpals, between the tibia and the astragalus and calcaneum, or among the metatarsals. Although juvenile characters have the potential to impede accurate identification of the specimen, morphological comparisons and cladistic analysis identify LNTU-WLMP-18 as most likely referable to the basal euornithine Archaeorhynchus, which would make the specimen the first juvenile bird from the Jehol Group that could be assigned to a specific taxon. Based on its size and the incomplete ossification of the bone surface, LNTU-WLMP-18 represents the smallest and therefore youngest known individual of this genus. A statistical comparison of limb proportions shows that the forelimbs of LNTU-WLMP-18 are significantly shorter than the hindlimbs, while the forelimbs are longer than the hindlimbs in subadult and adult individuals. This is different from the situation in some Enantiornithes, in which the forelimbs exceed the length of the hindlimbs even in hatchlings. Similar to Enantiornithes, Archaeorhynchus probably exhibit an early onset of flight ability, as indicated by the extensive wing plumage in LNTU-WLMP-18. The lack of gastroliths in the visceral cavity might indicate a dietary shift in Archaeorhynchus during ontogeny.